A review on the potential effects of combination treatments of anti-microbial and anti-inflammatory drugs towards male reproductive physiology in pneumonic bucks - Abd Manaf, Nur Athirah; Reduan, Mohd Farhan Hanif; Sabri, Jasni; Jesse, Faez Firdaus Abdullah; Ahmed Odhah, Mohammed Naji; Abdul Hamid, Fathin Faahimaah; Shaari, Rumaizi; Nordin, Muhammad Luqman; Muhammad Wakil, Abubakar; Kamaruzaman, Intan Noor Aina (Unique Scientific Publishers, 2023)
Pneumonia is the inflammation of lung parenchyma due to various organisms resulting in numerous manifestations and sequelae. The environment in the tropical regions provides optimal conditions for infection to occur in small ruminants. Mannheimiosis caused by Mannheimia haemolytica is the most frequent isolated bacteria causing pneumonia in small ruminants. The bacteria may cause an acute infection which can lead to death without proper diagnosis and treatment. To date, there are still scarce study on the effect of anti-microbial and anti-inflammatory treatments on reproductive physiology that warrants investigation. Hence, this review paper aims to focus on the possible effect of a combined usage of anti-microbial and anti-inflammatory treatments toward male reproductive physiology.